The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1039/b312129a
|View full text |Cite
|
Sign up to set email alerts
|

Novel and efficient synthesis of difficult sequence-containing peptides through O–N intramolecular acyl migration reaction of O-acyl isopeptides

Abstract: A novel and efficient method for the synthesis of difficult sequence-containing peptides has been developed based on the synthesis of O-acyl isopeptides followed by an O-N intramolecular acyl migration reaction, resulting in a remarkable improvement of the yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(152 citation statements)
references
References 17 publications
(11 reference statements)
5
145
0
2
Order By: Relevance
“…Depsi-peptide Aβ 1-42 was synthesized as previously described (47,48). At variance with the native peptide, the depsi-peptide is highly soluble and it has a much lower propensity to aggregate, thus preventing the spontaneous formation of seeds in the solution (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Depsi-peptide Aβ 1-42 was synthesized as previously described (47,48). At variance with the native peptide, the depsi-peptide is highly soluble and it has a much lower propensity to aggregate, thus preventing the spontaneous formation of seeds in the solution (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…As we will show here, switch-elements can be composed of depsipeptide (also called O-peptide or O-acyl isopeptide) units and/or pseudoprolines (CPro). So far, acyl transfer reactions have been the subject of extensive mechanistic studies, 24 and their role in protein biosynthesis and splicing, 25,26 peptide synthesis and solubilization, [27][28][29][30] prodrug design [31][32][33][34][35][36] and native chemoselective ligation strategies [37][38][39] has found broad attention. Our focus over the last few years was directed toward the elaboration of the concept of ''switch-peptides'' for the study of peptide self-assembly, secondary structure formation, and disruption.…”
Section: The Concept Of Switch-peptidesmentioning
confidence: 99%
“…N acyl migration. [5][6][7][8][9][10][11][12][13][14][15][16] However, because of the special synthetic and purification skills required to prepare the full-length Ab switch-peptides, such peptides are not suitable for use in highthroughput screening assays. Therefore, the development of reliable model systems that are readily accessible and adaptable to automated HTS is of particular interest to understanding the mechanism of amyloid formation and facilitating the discovery of aggregation inhibitors of Ab and other amyloid-forming proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we [5][6][7][8] and others [9][10][11][12] have shown that various steps along the amyloid formation pathway, including peptide/ protein misfolding, self-assembly, and amyloid formation and disassembly, can be triggered in a highly controllable manner through the incorporation of molecular switches into the amyloid-forming polypeptides, based on in situ intramolecular O! N acyl migration.…”
Section: Introductionmentioning
confidence: 99%